Mesostructured HSO3-functionalized TiO2-P2O5 sol-gel films prepared by evaporation induced self-assembly method with high proton conductivity. (10th August 2015) - Mosa, Jadra; Aparicio, Mario; Durán, Alicia; Castro, Yolanda
Abstract: Ordered mesoporous coatings, especially those structured as channels in three dimensions, could be applied as thin proton conducting membranes for application in proton exchange membrane fuel cells (PEMFC). This kind of materials shows high proton conductivity due to their favourable architecture with small and interconnected porosity. Transparent and crack-free TiO2 -P2 O5 sol-gel coatings with thickness around 200 nm were obtained by Evaporation induced self-assembly (EISA) method using Pluronic-127 as pore generating agent. X- Ray diffraction, SAXS and TEM analysis confirm the presence of ordered porous mesostructured films with a cubic Fd3m structures. Spectral ellipsometry and EEP measurements were used to determine the film thickness, refractive index, pore size, pore volume and specific surface area. EIS four-probe method was used to measure the proton conductivity. The textural properties (pore size in the range of mesoporous, high specific surface area and high pore volume) combined with inherent characteristics of sol-gel materials (high concentration of OH groups and release of protons mainly from Ti-OH and P-OH bonds) lead to a high proton conductivity, with maximum values around 0.11 and 0.20 S/cm depending on the phosphorous precursors (PCl3 or H3 PO4 ), measured at 140 °C and 80%RH. Acid functionalisation of mesoporous TiO2 -P2 O5 thin-films, with HSO3 groups, increases the proton conductivity up to 0.79 S/cm at 140 °C and 80%RH presenting high long-term stability. This work shows a processing guideline to design functionalized-inorganic mesostructured thin-films with high proton conductivity at high temperature.